Policy Regulation of Tourism Development with Integrated Agriculture in Bali - Anak Agung Dalem Ariyudha; Simon Nahak; Ni Made Jaya Senastri (Jurnal Hukum Prasada, 2021)
Balinese agriculture as a culture that becomes Balinese cultural tourism identity should still receive protection in line with the rapid development of tourism. However, in reality, the rapid and uncontrolled development of tourism is accused of having a big impact on the conversion of agricultural land in Bali. The disharmony that occurs can be used as a sign that the existing regulations have not been able to complete and integrate tourism and agricultural development. In this case, tourism development is not accompanied by legislation to protect agricultural land. This study aims to examine the legal arrangements related to tourism development with integrated agriculture in Bali and to examine the efforts that the government can take to integrate tourism development with agriculture in Bali. Empirical legal research is the type of this study. In addition, the approach used in this study is legislation approach, legal concept analysis approach and facts approach. The results of this study revealed that 1) the existing regulations relating to tourism development and agricultural development in Bali have provided an opportunity for integration between tourism development and agriculture in Bali, however, the regulations have not been optimal in preventing and reducing the negative impacts of rapid and uncontrolled tourism development. 2) In the perspective of ius constituendum, Bali tourism development must continue to provide protection for living cultural values, one of which is agriculture because basically Bali tourism development is based on Balinese culture which is imbued with the values of Tri Hita Karana and Sad Kerthi.